All-solid-state chloride ion battery and method for producing same
By doping alkali metal chloride in the lead chloride battery and mechanically grinding with the battery material, the problem of the capacity of all-solid chloride battery decreases after the number of cycles increases, achieving better cycle stability and battery performance.
Patent Information
- Application Number
- JP2021024029
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-18
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2041-02-18
AI Technical Summary
After the third charge and discharge of the non-aqueous chloride battery, the initial reversible capacity has dropped to about 50%, and the battery performance has declined due to the high solubility and poor cycle characteristics of the metal compound battery material in the polarized medium.
A solid electrolytic layer doped with lead chloride (PbCl2) and alkali metal chloride (MCl) is used to combine it with the positive electrode material and the negative electrode material through mechanical grinding to form an all-solid chloride battery.
The crystal structure of lead chloride is modified by doping alkali metal chloride, which improves the ionic conductivity and cyclic stability of the battery, and significantly improves the cyclic characteristics and battery performance of all-solid chloride batteries.
Smart Images

Figure 0007660807000001 
Figure 0007660807000002 
Figure 0007660807000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an all-solid-state chloride ion battery and a method for manufacturing the same. [Background technology]
[0002] Lithium-ion batteries are + This battery uses lithium as a carrier and is characterized by its high voltage. - Halide ion batteries, which use halide ions such as lithium ions as carriers, are said to have an energy density 1.5 to 3 times higher than current lithium ion batteries, and are expected to be promising candidates for post-lithium ion batteries. Among them, chloride ion batteries, which use chlorides, which are abundant resources, also have the advantage of being excellent in cost performance.
[0003] For example, Non-Patent Document 1 describes a method for making a BiCl 3 , 1M [OMIM]Cl in [BMIM]BF in non-aqueous electrolyte 4 The charge-discharge profile of a chloride ion battery using Li as the anode has been reported ([OMIM]Cl is the abbreviation for 1-methyl-3-octylimidazolium chloride, [BMIM]BF 4 (Is an abbreviation for 1-butyl-3-methylimidazolium tetrafluoroborate.) The theoretical capacity is 255 mAh / g, and the initial capacity is said to be about 180 mAh / g. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] X. Zhao, S. Ren, M. Bruns, and M. Fichtner, “Chloride ion battery: A new member in the rechargeable battery family”, J. Power Sources, 2014, 245, pp.706-711.
Summary of the Invention
Problems to be Solved by the Invention
[0005] However, according to the charge-discharge profile described in Non-Patent Document 1, in this non-aqueous chloride ion battery, the capacity decreases to about 50% of the initial reversible capacity by the third cycle. This is because the metal chloride used as the electrode material of the chloride ion battery has high solubility in polar solvents due to ionic bonding and has poor cycle characteristics.
[0006] Therefore, in view of the above problems, an object of the present invention is to provide a rechargeable all-solid-state chloride ion battery with improved cycle characteristics and a method for manufacturing the same.
Means for Solving the Problems
[0007] To achieve the above object, in one aspect of the present invention, there is provided an all-solid-state chloride ion battery including a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, wherein the solid electrolyte layer contains Pb 1-X M X Cl 2-X (wherein M is one or more alkali metal elements selected from the group consisting of Na, K, and Rb, and X is a number satisfying 0 < X < 1).
[0008] Further, in another aspect of the present invention, there is provided a method for manufacturing an all-solid-state chloride ion battery, including a step of subjecting a mixture containing PbCl 2 and MCl (where M is one or more alkali metal elements selected from the group consisting of Na, K, and Rb) to mechanical milling treatment to obtain a solid electrolyte, and a step of pressing with the solid electrolyte disposed between a positive electrode material and a negative electrode material to obtain an all-solid-state chloride ion battery including a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer.
Effects of the Invention
[0009] Thus, according to the present invention, PbCl 2 Pb doped with MCl 1-X M X Cl 2-X By employing a compound represented by the formula (I) as a solid electrolyte and configuring an all-solid-state chloride ion battery, it is possible to provide a chargeable and dischargeable all-solid-state chloride ion battery with improved cycle characteristics and a method for manufacturing the same. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view showing a schematic diagram of an embodiment of an all-solid-state chloride ion battery according to the present invention. [Diagram 2] FIG. 1 is a flow chart showing a part of an embodiment of a method for producing an all-solid-state chloride ion battery according to the present invention. [Diagram 3] 1 shows XRD patterns of an example of a solid electrolyte used in an all-solid-state chloride ion battery according to the present invention and a reference compound. [Figure 4] FIG. 2 is an exploded perspective view showing a schematic diagram of an HS cell used in an AC impedance test. [Diagram 5] FIG. 5 is a cross-sectional view showing a schematic diagram of a sample inserted into the HS cell of FIG. [Figure 6] 1 is a graph showing the results of an AC impedance test. [Figure 7] FIG. 2 is an exploded perspective view showing a schematic diagram of a PEEK cell used in a charge / discharge test. [Figure 8] 1 is a graph showing charge / discharge curves of the all-solid-state chloride ion battery of the example. [Figure 9] 1 is a graph showing cycle characteristics of an all-solid-state chloride ion battery of an example and a nonaqueous chloride ion battery of a reference example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of an all-solid-state chloride ion battery and a manufacturing method thereof according to the present invention will be described in detail with reference to the accompanying drawings.
[0012] As shown in FIG. 1, the all-solid-state chloride ion battery 10 of the present embodiment includes a positive electrode layer 13, a negative electrode layer 11, and a solid electrolyte layer 12 disposed between the positive electrode layer and the negative electrode layer. The solid electrolyte layer 12 contains a compound represented by Pb 1-X M X Cl 2-X (wherein M is one or more alkali metal elements selected from the group consisting of Na, K, and Rb, and X is a number satisfying 0 < X < 1). Optionally, a protective layer 14 may be further provided outside the positive electrode layer, that is, on the side opposite to the solid electrolyte layer. Each layer will be described in detail below.
[0013] The solid electrolyte layer 12 contains a compound represented by Pb 1-X M X Cl 2-X , which is obtained by doping lead chloride (PbCl 2 ) with an alkali metal chloride (MCl). By using PbCl 2 as the solid electrolyte, while suppressing the elution of the positive electrode active material (such as BiCl 3 ) in the positive electrode layer 13, and further doping it with MCl, the cycle characteristics of the all-solid-state chloride ion battery 10 can be improved. Although this is speculation, due to the doping of MCl, vacancies are formed at the Cl 2 sites in the crystal structure of PbCl - , and the ionic conductivity of Cl - is improved, so it is considered that the cycle characteristics are improved.
[0014] As long as the alkali metal chloride (MCl) used for doping is sodium (Na), potassium (K), rubidium (Rb) chloride or a combination of these chlorides, vacancies are formed at the Cl 2 sites in the crystal structure of PbCl - as described above, and the ionic conductivity of Cl - can be improved. X in the above formula representing the doping amount of MCl is preferably a number satisfying, for example, 0.01 ≦ X ≦ 0.1, and more preferably a number satisfying 0.01 ≦ X ≦ 0.03.
[0015] The solid electrolyte layer 12 is preferably a compact obtained by pressure-molding solid electrolyte particles. Since the solid electrolyte particles are not sintered and are chlorides, they are soft materials with excellent plasticity. By pressure-molding, the particles adhere to each other and can also adhere to the adjacent positive electrode layer 13 and negative electrode layer 11.
[0016] The thickness of the solid electrolyte layer 12 is preferably 1 μm or more, more preferably 100 μm or more. On the other hand, the thickness of the solid electrolyte layer 12 is preferably 1000 μm or less, more preferably 500 μm or less.
[0017] The positive electrode layer 13 includes an electrode composite material containing at least a positive electrode active material. As the positive electrode active material, metal chlorides are preferable. For example, chlorides of poor metals such as bismuth chloride (BiCl 3 ), gallium chloride (GaCl 3 ), indium chloride (InCl 3 ), chlorides of noble metals such as copper chloride (CuCl), silver chloride (AgCl), chlorides of iron group elements such as nickel chloride (NiCl 2 ), cobalt chloride (CoCl 2 ), iron chloride (FeCl 2 ), and other vanadium chloride (VCl 3 ) can be mentioned.
[0018] Since the electrode composite material of the positive electrode layer 13 generally does not show ionic conductivity, it may contain a solid electrolyte. As the solid electrolyte used in the electrode composite material of the positive electrode layer 13, similar to the solid electrolyte layer 12, Pb 1-X M X Cl 2-X (where M is one or more alkali metal elements selected from the group consisting of Na, K, and Rb, and X is a number satisfying 0 < X < 1) is preferable. Other solid electrolytes such as SnCl 2 and SrCl 2 , BaCl 2 etc. may also be used.
[0019] The proportion of the solid electrolyte in the electrode mixture of the positive electrode layer 13 is preferably 50 parts by mass or more, and more preferably 100 parts by mass or more, relative to 100 parts by mass of the positive electrode active material. On the other hand, the proportion of the solid electrolyte in the electrode mixture is preferably 200 parts by mass or less, and more preferably 150 parts by mass or less.
[0020] The electrode mixture of the positive electrode layer 13 generally does not have electronic conductivity, and may therefore contain a conductive agent. Examples of the conductive agent include carbon materials and metal compounds. Examples of the carbon material include carbon black (e.g., acetylene black, ketjen black, furnace black, etc.), graphite powder, and fibrous carbon materials. Examples of the metal compound include metals, metal alloys, and metal oxides that have electronic conductivity.
[0021] In the case of a carbon material, the proportion of the conductive agent in the electrode mixture of the positive electrode layer 13 is preferably 10 parts by mass or more, and more preferably 30 parts by mass or more, relative to 100 parts by mass of the positive electrode active material. On the other hand, the proportion of the conductive agent in the electrode mixture is preferably 100 parts by mass or less, and more preferably 50 parts by mass or less.
[0022] The positive electrode layer 13 is preferably a green compact obtained by pressure molding electrode mixture particles. The electrode mixture particles are not sintered and contain chlorides, making them a soft material with excellent plasticity. By pressure molding, the particles can adhere to each other and also to the adjacent solid electrolyte layer 12.
[0023] The thickness of the positive electrode layer 13 is preferably 1 μm or more, and more preferably 100 μm or more, while the thickness of the positive electrode layer 13 is preferably 1000 μm or less, and more preferably 500 μm or less.
[0024] The negative electrode layer 11 includes at least a negative electrode active material. As the negative electrode active material, an active material having a lower potential than the positive electrode active material is used. Examples of such active materials include simple metals such as lead (Pb) and tin (Sn), alloys, oxides thereof, and chlorides thereof.
[0025] The negative electrode layer 11 may be a compacted powder obtained by pressure-molding negative electrode active material particles, or may be a foil or plate of the negative electrode active material. The thickness of the negative electrode layer 11 is preferably 1 μm or more, more preferably 100 μm or more. On the other hand, the thickness of the negative electrode layer 11 is preferably 1000 μm or less, more preferably 500 μm or less.
[0026] The protective layer 14 is an optionally provided layer. By preventing the contact between the current collector and the electrode mixture with the protective layer 14 and suppressing the reaction between the two, the cycle characteristics can be further improved. The protective layer 14 preferably contains a protective material containing a solid electrolyte and a conductive agent. As the solid electrolyte used in the protective material, similar to the solid electrolyte layer 12, Pb 1-X M X Cl 2-X (wherein M is one or more alkali metal elements selected from the group consisting of Na, K, and Rb, and X is a number satisfying 0 < X < 1) is preferred. In addition, as the solid electrolyte, for example, SnCl 2 or SrCl 2 , BaCl 2 etc. may also be used. Further, as the conductive agent used in the protective material, the same carbon materials and metal compounds as those in the electrode mixture of the positive electrode layer 13 may be used.
[0027] The protective layer 14 is preferably a compacted powder obtained by pressure-molding protective material particles. Since the protective layer 14 does not participate in the charge and discharge capacity of the battery, its thickness is preferably thinner, preferably 500 μm or less, more preferably 100 μm or less. The lower limit of the thickness is not particularly limited, but for example, 1 μm or more is preferred.
[0028] According to the all-solid-state chloride ion battery 10 having such a configuration, since a compound represented by Pb 1-X M X Cl 2-X is used for the solid electrolyte of the solid electrolyte layer 12, BiCl of the positive electrode layer 13 3In addition, the ionic conductivity of the solid electrolyte layer 12 can be improved, and the cycle characteristics of the all-solid-state chloride ion battery 10 can be improved.
[0029] Next, a method for manufacturing the all-solid-state chloride ion battery according to the present embodiment will be described. In this method, as shown in FIG. 2, two raw materials 21a and 21b of the solid electrolyte are used, for example, PbCl 2 and KCl, and subjecting the mixture to mechanical milling to obtain a solid electrolyte 23; and a pressing step (not shown) in which the solid electrolyte 23 is placed between a positive electrode material and a negative electrode material and pressed to obtain an all-solid-state chloride ion battery.
[0030] This method may optionally further include a second mechanical milling step 25 of mixing the solid electrolyte 23 and the conductive agent 24 and subjecting the mixture to a mechanical milling process to obtain a conductive coating material 26 in which the solid electrolyte is coated with the conductive agent. The conductive coating material 26 can be used as a protective material for forming a protective layer, and in the pressing step, the protective material, the positive electrode material, the solid electrolyte, and the negative electrode material are arranged in this order and pressed to obtain an all-solid-state chloride ion battery.
[0031] In addition, this method may further include a third mechanical milling step 28 in which the conductive coating material 26 and the positive electrode active material 27 are mixed and the mixture is subjected to a mechanical milling process to obtain an electrode mixture 29. The electrode mixture 29 is used as a positive electrode material in the pressing step. Each of the above steps will be described in detail.
[0032] In the first mechanical milling step 22, first, Pb 1-X M X Cl 2-X In order to obtain the compound represented by the formula 2 Mix PbCl and MCl to obtain the desired composition. 2 Mix PbCl:MCl to make a 1-X:X ratio.2 By subjecting a mixture of each powder of and MCl to mechanical milling treatment, Pb 1-X M X Cl 2-X powders of the compound represented by can be obtained. X is a number satisfying 0 < X < 1. For example, as shown in FIG. 2, when KCl is used as MCl and X = 0.02, by mixing PbCl 2 and KCl at a mol ratio of 0.98:0.02, Pb 0.98 K 0.02 Cl 1.98 solid electrolyte 23 can be obtained.
[0033] As the mechanical milling treatment, for example, a ball mill, a vibration mill, a turbo mill, mechanofusion, a disk mill, etc. can be used. The rotation speed and treatment time of the mechanical milling treatment are such that each powder of the raw material PbCl 2 and MCl becomes a powder of the compound represented by Pb 1-X M X Cl 2-X It may be carried out until it becomes. For example, the rotation speed is 400 to 600 rpm and the treatment time is 3 to 12 hours. The mechanical milling treatment may be carried out dry or wet.
[0034] In the second mechanical milling step 25, first, the solid electrolyte 23 and the conductive agent 24 are mixed. The solid electrolyte 23 is preferably the solid electrolyte 23 obtained in the first mechanical milling step 22 as shown in FIG. 2, but the present invention is not limited thereto. Other solid electrolytes such as SnCl 2 and SrCl 2 , BaCl 2 etc. may be used. Specific examples of the conductive agent 24 and the blending ratio of the solid electrolyte 23 and the conductive agent 24 are described in the above description of the positive electrode layer, so the description here is omitted.
[0035] Then, the mixture containing the solid electrolyte 23 and the conductive agent 24 is subjected to mechanical milling to obtain the conductive coating material 26. The conductive coating material 26 is a collection of solid electrolyte particles whose surfaces are coated with a conductive agent. For example, as shown in FIG. 2, Pb 0.98 K 0.02 Cl 1.98 When carbon black (C) is used as the conductive agent 24, Pb is used as the conductive coating material 26. 0.98 K 0.02 Cl 1.98 A collection of particles whose surfaces are coated with carbon can be obtained. 0.98 K 0.02 Cl 1.98 This is expressed as / C.
[0036] The mechanical milling process is performed using the same equipment as in the first mechanical milling process. The rotation speed and processing time of the mechanical milling process may be such that the surface of the solid electrolyte particles is covered with the conductive agent, and for example, the rotation speed is 400 to 600 rpm and the processing time is 3 to 12 hours. The mechanical milling process may be performed in a dry or wet manner.
[0037] In the third mechanical milling step 28, first, the conductive coating material 26 and the positive electrode active material 27 are mixed. As shown in FIG. 2, the conductive coating material 26 obtained in the second mechanical milling step 25 is preferable, but the present invention is not limited thereto, and a collection of particles in which particles of other solid electrolytes are coated with other conductive agents may be used. The mixing ratio of the conductive coating material 26 and the positive electrode active material 27 is determined by the ratio of the mass of the solid electrolyte in the conductive coating material 26 to the mass of the positive electrode active material. The ratio of the solid electrolyte to the positive electrode active material and specific examples of the positive electrode active material are described in the above description of the positive electrode layer, so that the description here is omitted.
[0038] Then, the mixture containing the conductive coating material 26 and the positive electrode active material 27 is subjected to mechanical milling to obtain an electrode mixture 29. The electrode mixture 29 is a mixture of the conductive coating material and the positive electrode active material. For example, as shown in FIG. 2, Pb 0.98 K 0.02 Cl 1.98 / C, and bismuth chloride (BiCl 3 ) is used, the resulting electrode mixture 29 is BiCl 3 / Pb 0.98 K 0.02 Cl 1.98 This is expressed as / C.
[0039] The mechanical milling process is performed using the same equipment as in the first mechanical milling process. The rotation speed and processing time of the mechanical milling process may be set to a value sufficient for obtaining a mixture of the conductive coating material and the positive electrode active material, and may be set to, for example, 100 to 400 rpm and 3 to 12 hours. The mechanical milling process may be performed in a dry or wet manner.
[0040] In the pressing step (not shown), the positive electrode mixture 29 and the solid electrolyte 23 obtained as above, and the negative electrode material are arranged in this order and pressed to form an all-solid-state chloride ion battery having a positive electrode layer, a solid electrolyte layer, and a negative electrode layer in this order. A negative electrode active material can be used as the negative electrode material. The negative electrode active material is described in the description of the negative electrode layer above, so a description thereof is omitted here. In order to form an all-solid-state chloride ion battery further including a protective layer, the conductive coating material 26 obtained as above, the positive electrode mixture 29 and the solid electrolyte 23, and the negative electrode material are arranged in this order and pressed.
[0041] The pressure during pressing may be any pressure that can cause plastic deformation of the particles of the solid electrolyte 23 obtained above to form a dense solid electrolyte layer, and is preferably, for example, 255 to 510 MPa. The temperature during pressing may be room temperature. Heat treatment such as calcination is not required.
[0042] According to the manufacturing method of the all-solid-state chloride ion battery using such a process, the solid electrolyte 23, the electrode mixture 29, and the conductive coating material, which are the materials of the solid electrolyte layer, the positive electrode layer, and the optional protective layer constituting the battery, can be efficiently obtained, and an all-solid-state chloride ion battery capable of reversible charging and discharging can be obtained by a simple manufacturing process of pressure-molding the constituent materials of the battery. In addition, since there is no need for sintering, it is also possible to avoid high resistance due to side reactions. EXAMPLES
[0043] [1. Solid electrolyte] PbCl in an agate mortar 2 and KCl were mixed in three molar ratios, 0.99:0.01, 0.98:0.02, and 0.97:0.03, and each mixture was subjected to mechanical milling at 600 rpm for 12 hours in a planetary ball mill (Fritch, Premium line P-7). XRD patterns were obtained for each sample using an X-ray diffraction (XRD) measuring device (Rigaku, product number: Miniflex600). For comparison, PbCl 2 The XRD pattern of the sample alone was also obtained, and the results are shown in Figure 3.
[0044] In addition, an AC impedance test was performed on each of the obtained samples using an HS cell (manufactured by Hosen Co., Ltd.) shown in FIG. 4. As shown in FIG. 4, the HS cell 40 is a cell for battery evaluation tests, in which a flanged cell container 41, a sample cell 50, a cylindrical guide 42, a flanged cell lid 43, and a pressing member 44 are stacked in order, and the flanged cell container 41 and the flanged cell lid 43 are fixed with four sets of bolts 46 and nuts 47. As shown in FIG. 5, the sample cell 50 was first prepared by uniaxially pressurizing the above sample at 510 MPa to prepare a pellet 52 with a diameter of 10 mm, and Pt layers 51a and 51b were formed on both sides of the pellet 52 by Pt sputtering. Then, an AC impedance test was performed in the temperature range of 25 to 160°C. For comparison, PbCl 2 A sample cell was also prepared and tested for the same, and the results are shown in Figure 6.
[0045] The crystal structure was identified by the XRD pattern shown in Figure 3. From the analysis of the XRD pattern, PbCl 2 KCl doped Pb 1-X M X Cl 2-X It was found that the crystal structure of (X=0.01, 0.02, 0.03) did not change before and after ball milling, regardless of the amount of KCl doped.
[0046] In addition, from the Arrhenius plot shown in Figure 6, PbCl 2 The KCl doped one has a higher Cl content than the non-KCl doped one. - It was found that the ionic conductivity was improved by 2 to 3 orders of magnitude. In particular, the PbCl 2 Cl is the highest - It has an ionic conductivity of 2.28×10 at 160oC. -4 This was due to the doping of KCl. 2 In the crystal structure of - Vacancies are formed at the Cl sites. - This is believed to be due to the improved ionic conductivity of the
[0047] [2. All-solid-state chloride-ion batteries] The sample obtained above was used as a solid electrolyte to fabricate an all-solid-state chloride ion battery, and a charge / discharge test was performed.
[0048] First, PbCl 2 A sample doped with 2 mol% KCl (Pb 0.98 M 0.02 Cl 1.98 ) was mixed with acetylene black in a mass ratio of 5:1. This mixture was then subjected to mechanical milling in a planetary ball mill at 600 rpm for 12 hours to obtain a carbon coating material (Pb 0.98 M 0.02 Cl 1.98 / C) was obtained. 3The mixture was then subjected to mechanical milling in a planetary ball mill at 150 rpm for 12 hours to obtain an electrode composite (BiCl 3 / Pb 0.98 M 0.02 Cl 1.98 / C) was prepared.
[0049] The solid electrolyte is PbCl 2 170 mg of a sample doped with 2 mol% KCl was used, 30 mg of the above carbon coating material was used as the protective material, 30 mg of the above electrode mixture was used as the positive electrode material, and a Pb plate was used as the negative electrode material. The negative electrode Pb was charged in an excess amount relative to the mass of the electrode mixture, which was the positive electrode. The protective material, positive electrode material, solid electrolyte, and negative electrode material were then arranged in this order, and pressed at room temperature with a pressure of 510 MPa to obtain a coin-shaped all-solid-state cell with a diameter of 10 mm, in which the protective layer, positive electrode layer, solid electrolyte layer, and negative electrode layer were stacked in this order.
[0050] A charge-discharge test was carried out on the all-solid-state cell thus obtained using a PEEK cell (manufactured by MTI Japan) shown in FIG. 7. As shown in FIG. 7, the PEEK cell 70 is a cell for battery evaluation tests, which is prepared by stacking a negative electrode side plate 71 made of polyether ether ketone (PEEK), an all-solid-state cell 10', a cylindrical guide 72, and a positive electrode side plate 73 made of PEEK in that order. As shown in FIG. 1, the all-solid-state cell 10' is a cell in which a protective layer 14, a positive electrode layer 13, a solid electrolyte layer 12, and a negative electrode layer 11 are stacked in that order. Then, the all-solid-state cell 10' is stacked in a glove box at 160° C. and 0.1 mA / cm. 2 The charge and discharge tests were carried out under the following conditions. The results are shown in Figures 8 and 9.
[0051] The charge-discharge profile of the all-solid-state cell is shown in Figure 8. As shown in Figure 8, the initial discharge and charge capacities were 187 mAh / g and 158 mAh / g, respectively, which correspond to approximately 2.2 and 1.9 electron reactions, respectively.
[0052] Fig. 9 shows the cycle characteristics of the all-solid-state cell (Example). As shown in Fig. 9, the all-solid-state cell showed relatively good cycle characteristics, and even at the 30th cycle, it was found that the initial reversible capacity was maintained at about 85%. For comparison, a BiCl 3 The results of a charge-discharge test of a non-aqueous cell using Li as the negative electrode and an ionic liquid of 1 M 1-methyl-3-octylimidazolium chloride in a solvent of 1-butyl-3-methylimidazolium tetrafluoroborate as the electrolyte (Non-Patent Document 1) are also shown as a reference in Fig. 9. As shown in Fig. 9, it has been reported that the initial reversible capacity of this non-aqueous cell decreases to about 50% at the third cycle, and it has been made clear that the cycle characteristics of the all-solid-state chloride ion battery of the present invention are significantly improved. [Explanation of symbols]
[0053] 10 All-solid-state chloride-ion battery 11 Negative electrode layer 12 Solid electrolyte layer 13 Positive electrode layer 14 Protective layer 22 First mechanical milling process 25 Second mechanical milling process 28 The third mechanical milling process 40 HS Cell 50 Sample Cell 70 PEEK Cells
Claims
1. An all-solid-state chloride ion battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, The solid electrolyte layer is Pb 1-X M X C 2-X (wherein M is one or more alkali metal elements selected from the group consisting of Na, K and Rb, and X is a number satisfying 0.01≦X≦0.1).
2. 2. The all-solid-state chloride ion battery according to claim 1, wherein X in the formula is a number that satisfies 0.01≦X≦0.
03.
3. The positive electrode layer further includes a protective layer on the opposite side of the solid electrolyte layer, the protective layer being made of Pb 1-X M X C 2-X 3. The all-solid-state chloride ion battery according to claim 1, comprising a compound represented by the formula: (wherein M is one or more alkali metal elements selected from the group consisting of Na, K and Rb, and X is a number satisfying 0<X<1), and a conductive agent.
4. PbCl 2 and MCl (M is one or more alkali metal elements selected from the group consisting of Na, K, and Rb) in a molar ratio of 1-X:X (=PbCl 2 :MCl) (X is a number that satisfies 0.01≦X≦0.1), to obtain a solid electrolyte; a step of pressing the positive electrode material and the negative electrode material with the solid electrolyte disposed therebetween to obtain an all-solid-state chloride ion battery including a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer; A method for producing an all-solid-state chloride ion battery comprising:
5. 5. The method for producing an all-solid-state chloride ion battery according to claim 4, further comprising the step of subjecting a mixture containing a part of the solid electrolyte and a positive electrode active material containing a metal chloride to a mechanical milling process to obtain an electrode mixture as the positive electrode material.
6. The method further includes a step of subjecting the mixture containing another part of the solid electrolyte and the conductive agent to a mechanical milling process to obtain a protective material, 6. The method for producing an all-solid-state chloride ion battery according to claim 4 or 5, wherein in the pressing step, pressing is performed while the protective material, the positive electrode material, the solid electrolyte, and the negative electrode material are arranged in this order, to obtain an all-solid-state chloride ion battery in which a protective layer, the positive electrode layer, the solid electrolyte layer, and the negative electrode layer are stacked in this order.
Citation Information
Patent Citations
Electrochemical hydrogen-catalyst power system
CN102906925A
Electrochemical element made of polymer solid electrolyte-halogenide solid electrolyte-metal electrode laminated body
JP1989076685A
Alkali ion electrolyte composition
JP2013179025A